Polar-radii graphs a geometric-invariant, shape-based approach to handwritten text recognition - Oche, Jonathan Sinogaya (2002)
In recognizing handwritten texts, one of the major consideration is the inherent variability of human handwriting. The problem of variability in handwriting due to geometric distortion of letters by scale and rotation is addressed in this thesis using the Polar-Radii Graph scheme. Scale and rotation invariant, the PRG image coder is used to encode handwritten texts. The PRG of a handwritten character is a functional representation that can be used to describe and regenerate the character with appropriate accuracy. It shows the relationship between the relative distances from the character's centroid to points along the outer boundary as a function of angle. The handwritten texts are limited to compose only of at most two characters. The characters may or may not be connected. They can be any of the 52 upper and lowercase character classes of the English alphabet. A handwriting recognizer was developed to implement this problem and was tested using both single and double-character handwritings obtained from 500 different writers. The test for 26,000 single-character handwritings yielded a recognition rate of 90.22%. The test for 26,000 single character handwritings yielded a recognition rate of 90.22%. The test for 1,500 double-character handwritings yielded a recognition rate of 87.08